2011
DOI: 10.1136/annrheumdis-2011-200395
|View full text |Cite
|
Sign up to set email alerts
|

Tocilizumab inhibits progression of joint damage in rheumatoid arthritis irrespective of its anti-inflammatory effects: disassociation of the link between inflammation and destruction

Abstract: BackgroundTreatment with tumour necrosis factor inhibitors (TNF-i) plus methotrexate (MTX), but not MTX monotherapy alone, inhibits joint damage progression even at higher levels of disease activity. Such disassociation of disease activity and structural damage has not been shown for biological agents other than TNF-i.ObjectivesTo evaluate whether interleukin 6 (IL-6) inhibition with tocilizumab (TCZ) interferes with joint destruction beyond its effects on disease activity.MethodsA random 90% sample of data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
1
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(86 citation statements)
references
References 43 publications
4
75
1
6
Order By: Relevance
“…In addition to clinical efficacy, several studies have demonstrated the ability of tocilizumab to reduce radiographic progression (Nishimoto et al, 2007;Kremer et al, 2011;Dougados et al, 2013). Radiographic progression is reduced with tocilizumab even in the presence of persistent synovitis or high disease activity (Smolen et al, 2012), a feature also described with anti-TNF agents and rituximab (Landewe et al, 2006;Emery et al, 2009;Smolen et al, 2009;Aletaha et al, 2013).…”
Section: B Anti-interleukin-6 Drugs In Rheumatoid Arthritismentioning
confidence: 98%
“…In addition to clinical efficacy, several studies have demonstrated the ability of tocilizumab to reduce radiographic progression (Nishimoto et al, 2007;Kremer et al, 2011;Dougados et al, 2013). Radiographic progression is reduced with tocilizumab even in the presence of persistent synovitis or high disease activity (Smolen et al, 2012), a feature also described with anti-TNF agents and rituximab (Landewe et al, 2006;Emery et al, 2009;Smolen et al, 2009;Aletaha et al, 2013).…”
Section: B Anti-interleukin-6 Drugs In Rheumatoid Arthritismentioning
confidence: 98%
“…Ultrasound (US) and magnetic resonance imaging (MRI) evaluations are more sensitive techniques to identify synovitis than clinical examination and are better than conventional radiography to detect bone erosion (3). The exact position of US in RA management has been recently clarified (4).…”
Section: Supported By the Espoir (Etude Et Suivi Des Polyarthritesmentioning
confidence: 99%
“…Elevated levels of IL-6 have been reported in the serum and synovial fluid of patients with RA and have been found to correlate with inflammation and disease activity (8)(9)(10). A humanized inhibitor of IL-6 activity (11,12) has been shown to be effective in RA, administered either as monotherapy or in combination with methotrexate (MTX) and other nonbiologic DMARDs (13)(14)(15)(16)(17)(18). Sarilumab is a fully human anti-IL-6Ra monoclonal antibody that binds membranebound and soluble human IL-6R with high affinity, thereby blocking IL-6-mediated cis-and trans-signaling, with no evidence of complement-dependent or antibodydependent cell-mediated cytotoxicity (19).…”
mentioning
confidence: 99%